(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the outcomes of thoracoscopic surgery in treating lung and bronchial lesions in children at Children’s Hospital 2 from 2017 to 2024. Methods: A retrospective descriptive study was conducted on 67 children (68 surgical cases) who underwent thoracoscopic surgery for lung and bronchial lesion resection. Clinical, paraclinical, surgical characteristics, and treatment outcomes were collected and analyzed. Results: Congenital pulmonary airway malformation (CPAM) was the most common lesion (57.4%), followed by pulmonary sequestration (39.7%) and one case of bronchial tumor (1.5%). Prenatal diagnosis was achieved in 65.6% of cases. The mean surgical duration was 122.4 ± 54.5 minutes, with a conversion rate to open surgery of 4.4% and successful single-lung ventilation in 44.7% of cases. The average intensive care unit stay was 2.7 days, chest tube removal occurred after 3.9 days, and hospital discharge after 11.4 days. The most common postoperative complication was pneumothorax (17.6%), mostly self-limiting. Two cases (2.9%) required reoperation. No mortality was recorded. Conclusion: Thoracoscopic surgery is a safe and effective method for treating lung and bronchial lesions in children, with a low complication rate and no mortality.